2020
DOI: 10.1111/modl.12670
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Challenges of L2 Reading: Self‐Efficacy, Self‐Regulatory Reading Strategies, and Learner Profiles

Abstract: Reading in a foreign language has value for learners as a potentially rich source of input as well as enjoyment. It requires persistence, however. Within models of self-regulated learning, persistence relates to learners' self-efficacy and use of strategies to aid task completion and regulation of engagement. Yet the relationship between self-efficacy and self-regulatory strategies is underexplored for second language (L2) reading, despite some intervention studies finding that instruction aimed at improving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Self-regulatory skills are of limited value if one does not possess a strong sense of self-efficacy to engage and persist in the learning activity (Zimmerman, 2000;Schunk and Pajares, 2010;Schunk and Usher, 2012). Researchers thus posit that self-regulatory behavior and self-efficacy are integrated during learners' engagement in learning rather than distinct entities (Kaplan et al, 2009;Panadero, 2017;Graham et al, 2020b). For instance, Zimmerman's (2013) model of SRL describes a reciprocal relation between strategy use and self-efficacy, in which selfefficacy underlies the forethought phrase of goal setting and strategic planning and affect the efforts and attention devoted to the different phases of SRL learning (Zimmerman and Risemberg, 1997;Bruning et al, 2013;Bai and Wang, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-regulatory skills are of limited value if one does not possess a strong sense of self-efficacy to engage and persist in the learning activity (Zimmerman, 2000;Schunk and Pajares, 2010;Schunk and Usher, 2012). Researchers thus posit that self-regulatory behavior and self-efficacy are integrated during learners' engagement in learning rather than distinct entities (Kaplan et al, 2009;Panadero, 2017;Graham et al, 2020b). For instance, Zimmerman's (2013) model of SRL describes a reciprocal relation between strategy use and self-efficacy, in which selfefficacy underlies the forethought phrase of goal setting and strategic planning and affect the efforts and attention devoted to the different phases of SRL learning (Zimmerman and Risemberg, 1997;Bruning et al, 2013;Bai and Wang, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SRL is described as a strategic, dynamic process whereby learners activate and sustain their cognitions, motivations, and behaviors toward the attainment of learning goals (Schunk and Zimmerman, 2007 ; Zimmerman and Schunk, 2011 ). Many researchers thus leveraged on SRL-strategies-based interventions with the aim to support learners' knowledge of SRL and their engagement in SRL activities, and positive effects on students' L2 learning achievements were reported (e.g., Graham et al, 2020b ; Teng and Zhang, 2020 ; Bai and Wang, 2021 ; Teng, 2022 ). Furthermore, the experience of deploying SRL strategies to successfully complete tasks could convey to learners' beliefs of their competence in L2, thus positively affecting their self-efficacy (Schunk and Zimmerman, 1997 ; Bai and Guo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“… Bandura (1997) mentioned that four different sources can help to raise one’s self-efficacy: previous successful experience of participating in the same or similar activities, seeing others dealing with the same task easily, encouragement or recognition from others and the positive emotional status of one’s own. In the context of learning a second language, studies have shown that L2 learners with a high level of self-efficacy are those who receive encouragement and assistance by the instructors ( Graham et al, 2020 ; Xu et al, 2022 ), actively learn from a leading student ( Wang and Sun, 2020 ) and willingly apply more learning strategies to enhance their involvement in class ( Anam and Stracke, 2020 ). The study of Xu et al (2022) showed that after an intensive summer English training program, where all four sources can be found, learners’ self-efficacy was largely improved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A reader's prior knowledge (Kintsch, 1998), cognitive skills and repertoire of reading strategies (Duke & Pearson, 2002), reading proficiency (Mills et al, 2006), the text, reading context and motivation (Afflerbach & Cho, 2010), and the online/offline reading modes (Forzani et al, 2021) are among the determining factors in comprehending a reading. Being literate in a second language (L2) or foreign language (FL) requires an individual to overcome several challenges as opposed to reading in L1 due to the intricacies of L2/FL reading and the complex cognitive processes (Graham et al, 2020;Murad Sani & Zain, 2011). For example, linguistic, affective and motivational factors affect reading comprehension in L2/FL (Grabe & Stoller, 2019;Li & Wang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, linguistic, affective and motivational factors affect reading comprehension in L2/FL (Grabe & Stoller, 2019;Li & Wang, 2010). Additionally, other key factors such as comprehension strategies (Taylor, 2014), language proficiency (Fung & Macaro, 2019), self-regulatory reading strategies (Macaro & Erler, 2008), self-efficacy and strategy use (Zimmerman, 2013), and strategy instruction for developing self-efficacy (Gu, 2019) are vital to reading achievement in L2/FL (Graham et al, 2020).…”
Section: Introductionmentioning
confidence: 99%